The charm bracelet : a novel - Shipman, Viola (Thomas Dunne Books, 2016)
"Through an heirloom charm bracelet three women will rediscover the importance of family, love, faith, friends, fun and a passion for living as the magic of each charm changes their lives. Lolly, still lives in the family cabin on Lost Land Lake where her mother gave her the charm bracelet that would become Lolly's talisman and connection to family past and Lolly hopes the present, but her daughter, Arden, and granddaughter, Lauren, haven't visited in years and time is running out for Lolly. Arden, couldn't wait to leave her small town life behind for Chicago, but now divorced and burned out at work, she's simply trying to make it from day to day. In the rush of life she's let the years and all the things she once enjoyed slip away. When she receives an unexpected phone call about her mother she must decide if she can face going home. Lauren, a talented young painter buries her passion to study business in the hopes of helping her mother after she discovers that her father left Arden struggling to make ends meet, but Lauren is slowly dying inside and doesn't know how to tell her mother the truth"--